2023
DOI: 10.3389/fpubh.2022.1031655
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of self-care behaviors and glycemic control among patients with type 2 diabetes mellitus

Abstract: AimsThis study used the Extended Theory of Reasoned Action (ETRA) to predict self-care behaviors and HbA1c among patients with type 2 diabetes in Iran.Materials and methodsA cross-sectional study was performed using a multistage random sample. A total of 240 patients with type 2 diabetes, who were referred to the diabetes healthcare centers in Chaldoran, participated in the research. Instruments consisting of standardized questionnaires were used based on the Extended Theory of Reasoned Action (ETRA) construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Best predictor. PI effectively promotes the generation of PB in health behaviors, which is consistent with previous findings in the intention-behavior relationship that reasonable intentions may provide better behavior prediction (100)(101)(102). This provides strong evidence for the decisive impact of PI on PB.…”
Section: Predictive Factors Of Health Screening Behaviorsupporting
confidence: 90%
“…Best predictor. PI effectively promotes the generation of PB in health behaviors, which is consistent with previous findings in the intention-behavior relationship that reasonable intentions may provide better behavior prediction (100)(101)(102). This provides strong evidence for the decisive impact of PI on PB.…”
Section: Predictive Factors Of Health Screening Behaviorsupporting
confidence: 90%
“…The finding of increased self-efficacy has important implications, as this is considered a key component to behavior change and also to self-management across a wide spectrum of conditions including sedentariness [ 25 ], hypertension [ 26 ], and diabetes [ 27 ]. It has been similarly studied as a potential indicator of healthy behavior changes in other gardening interventions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etymology of the word 'healing' suggests 'building a whole' or 'unifying' a community, and group participation has also been reported to be effective in emotional exchanges with humans (31,32). It has also been reported that these backgrounds can be used as social support to improve health through self-efficacy and self-care (33)(34)(35). Building a relationship of trust between the staff involved in health education and the participants may increase the rate of exercise continuation, leading to improved health and quality of life.…”
Section: Discussionmentioning
confidence: 99%